A survey on policies, modelling and security of cyber‐physical systems in smart grids. Issue 4 (6th December 2021) - Wang, Qin; Zhang, Guangyuan; Wen, Fushuan
Abstract: A more reliable, efficient, and resilient smart grid depends on the applications of advanced information and communication technologies to support new functions and controls. The critical infrastructure of a smart grid consists of some major components such as monitoring, controls, communication protocol and software. The cyber‐physical system (CPS), which integrates these components, is an important enabler for the expected transition of the energy system driven by decarbonization, digitalization and decentralization. This paper provides an overview of the policy drivers and barriers for the implementation of CPS in power systems. With the vast deployment of distributed energy resources (DERs), there is increasing demand to model the hardware, software and their interactions in the smart grid environment. This paper reviews the modelling and applications of intelligent CPS for decentralized energy systems. The integration of DERs and the supportive infrastructure make modern power systems more vulnerable and less reliable to external threats such as terrorist intrusion. There are growing concerns over the risk of cyber‐attacks in mart grids. This paper surveys the latest progress on critical infrastructure identification and protection, as well as risk assessment and mitigation methods for cyber‐attacks. Finally, some advanced issues in cyber‐physical energy systems are addressed.